School, Family, and Community Dynamics: Challenges and Opportunities from Pandemic to Post-Pandemic - Sereño, Ana Rubi (JPAIR Multidisciplinary Research, 2023)
Two consecutive years have passed since educational institutions globally were closed due to the Covid-19 pandemic. In the first quarter of 2020, classes at all levels in the Philippines were suspended, and alternative means of completing the respective school year have been very challenging. Implementing Modular Distance Learning (MDL) was the best option for the Department of Education to continue learning. This phenomenological research described the school, family, and community dynamics, the challenges experienced, and the opportunities encountered in transitioning to face-to-face classes in Bislig City Division. The researcher used an interview guide to gather the responses from individual interviews and focus group discussions. Word cloud applications for the categorization of themes were also used. Findings showed that the COVID-19 pandemic has snatched the students’ significant mental, emotional, and physical health; challenges of infection, adjustment to the new normal, and learning gaps brought about by the distance learning modality were related. However, assurance of students’ holistic preparedness and support to school were the major themes that emerged. Thus, the role of family, school, and community were interconnected and deemed essential in promoting better learning outcomes. Opportunities were also evident amidst the educational crisis. Its advantages were strong collaboration among stakeholders, promotion of economic activities, and a safe learning environment.